Dendrobium nobile Lindl. Polysaccharides protect fibroblasts against UVA-induced photoaging via JNK/c-Jun/MMPs pathway. (15th November 2022) - Li, Wei; Mu, Xingrui; Wu, Xingqian; He, Wenjie; Liu, Ye; Liu, Yiqiu; Deng, Junyu; Nie, Xuqiang
Abstract: Ethnopharmacological relevance: Dendrobium nobile Lindl. is an orchid species that is found throughout Asia, including Thailand, Laos, Vietnam, and China. It has been used to treat tumors, hyperglycemia, hyperlipidemia, and neurological disorders caused by aging in recent decades. Aim of the study: To investigate the antagonistic effect of Dendrobium nobile Lindl. Polysaccharides (DNLP) on UVA-induced photoaging of Human foreskin fibroblasts (HFF-1) and explore its possible anti-aging mechanisms. Materials and methods: An in vitro photoaging model of dermal fibroblasts was established with multiple UVA irradiations. Fibroblasts were treated with 0.06 mg/ml, 0.18 mg/ml, 0.54 mg/ml of DNLP one day before photodamage induction. The levels of reactive oxygen species (ROS), Malondialdehyde (MDA), cell viability and longevity, Superoxide Dismutase (SOD), Catalase (CAT), and Glutathione peroxidase (GSH-Px) enzymatic activities were determined. We examined how DNLP ameliorates the effects of photoaging, the JNK/c-Fos/c-Jun pathway, senescence-associated β-galactosidase (SA-β-Gal), and MMP expression levels were measured. Results: UVA irradiation reduced the viability, lifespan, and proliferation of HFF-1 cells, increased ROS and lipid peroxidation and decreased the activities of free radical scavenging enzyme systems SOD, CAT, and GSH-Px. DNLP treatment can reverse UVA damage, reduce SA-β-Gal expression, reduce phosphorylation activation of the JNK/c-Fos/c-Jun pathway and inhibit MMP-1, MMP-2 MMP-3, and MMP-9 protein expression. Conclusions: DNLP can effectively inhibit UVA damage to HFF-1 and prevent cell senescence. Its mechanism of action may increase antioxidant enzyme activity while inhibiting JNK pathway activation and MMPs expression. Graphical abstract: Image 1 Highlights: UVA irradiation of dermal fibroblasts impairs the activity of antioxidant enzymes. Dendrobium nobile Lindl. Polysaccharides can inhibit UVA damage to HFF-1 and prevent cell senescence. The mechanism might be related to the regulation of JNK/c-Jun/MMPs Pathway.